ANALYSIS OF DEVELOPMENT OF SAVINGS AND LOANS UNIT IN THE COOPERATIVE OF THE REPUBLIC OF INDONESIA PROSPEROUS OF CIREBON DISTRICT - Agus Arifin; Fauziah; Yolanda Rakawati; Taufik Ridwan (Syntax Corporation Indonesia, 2020)
The development of the savings and loan cooperativesystem today needs an increase that can make the system evenbetter and correct according to the rules and laws of theRepublic of Indonesia. The current cooperative systemprovides many loans and savings so that to make a goodsystem it must do research that discusses it.Thus in this study discusses how the analysis of thedevelopment of cooperative systems in the savings and loanunits of the cooperative of the Republic of Indonesiaprosperous employees of Cirebon district, in this studyexplained how the process and review of the savings and loancooperative system so far, its development, role and what arethe factors that exist in the system this savings and loancooperativeKeyword: Analysis, Cooperative Unit, Development ofSaving.